Inhibition of polymorphonuclear leucocyte functions in vivo by Yersinia enterocolitica lipopolysaccharide. - Hartiala, K T (1989)
A single intravenous injection of 5 micrograms of Yersinia enterocolitica lipopolysaccharide (LPS) inhibits rabbit polymorphonuclear leucocyte (PMN) chemotaxis, enzyme secretion, and respiratory burst activation in response to partially purified rabbit C5a and leucotriene B4 (LTB4). Respiratory burst activation is also inhibited in response to platelet activating factor (PAF). In contrast, all these responses to n-formyl-methionyl-leucyl-phenylalanine (FMLP) remain unaltered. This LPS does not modulate PMN activation in vitro or activate the respiratory burst. Thus Y enterocolitica LPS acts in vivo by inhibiting PMN responses to endogenous mediators of inflammation. This inhibition presumably impairs the elimination of pathogens and might, therefore, provide favourable conditions for induction by bacteria of further immunological consequences.